ARGAMASSAS AUTOADENSÁVEIS: INFLUÊNCIA DO TIPO DE ADIÇÃO MINERAL - Porto, Maria Fernanda; Cofani, Franciele Stefani; Filla, Gustavo de Pinho Tavares; Toralles, Berenice Martins (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper aims to compare the effects of different types of mineral additions, in self compacting mortars, in relation to the properties in fresh state. For the study of this influence, the flow test was performed in two different mortars with three samples each containing different mineral additives. Through the scattering data obtained, it was observed that the addition of dolomitic limestone produces the most fluid mortars with little exudation during the tests. While the use of active silica causes a significant decrease in the flow ability, but with a greater control over the exudation of the materials. Finally, the addition of the basalt powder presented an intermediate character between the two other additions.